White Matter Microstructural Damage on Diffusion Tensor Imaging in Cerebral Small Vessel Disease: Clinical Consequences. Issue 6 (June 2016) - Pasi, Marco; van Uden, Inge W.M.; Tuladhar, Anil M.; de Leeuw, Frank-Erik; Pantoni, Leonardo
Abstract : Supplemental Digital Content is available in the text.